Incidental detection of primary hepatocellular carcinoma on 18F-prostate-specific membrane antigen-1007 positron emission tomography/computed tomography imaging in a patient with prostate cancer: A case report. Issue 41 (9th October 2020) - Zhao, Hongguang; Li, Yinghua; Hou, Sen; Dai, Yuyin; Lin, Chenghe; Xu, Songbai
Abstract: Rationale: Prostate-specific membrane antigen positron emission tomography-computed tomography ( 18 F-PSMA-1007 PET/CT) imaging is an emerging method for the diagnosis of prostate cancer (PC), but its efficiency in detecting other accompanying diseases has rarely been investigated. Patient concerns: A 77-year-old man presented with a complaint of bone pain throughout his entire body lasting for 2 weeks. Routine preoperative whole-body bone scanning revealed multiple osteogenic metastases. His alpha-fetoprotein and prostate-specific antigen levels were 108.2 ng/mL and 53.32 ng/mL, respectively. 18 F-PSMA-1007 PET/CT imaging revealed high tracer uptake in the primary lesion in the liver and the peripheral zone of the prostate. Diagnoses: Due to the results from imaging and pathological examinations, a diagnosis of PC with multiple bone metastases accompanied by primary hepatocellular carcinoma was made. Interventions: Taking into consideration the patient's age, interventional therapy was performed for the liver lesion, whereas the prostate and bone lesions were treated with endocrine therapy. Outcomes: The patient recovered well and was discharged uneventfully postoperatively. The patient was also doing well at the 6-month follow-up. Lessons: PSMA-PET/CT imaging results must be interpreted cautiously when the uptake of PSMA increases in a single lesion instead of the most common sites of PC metastasis. Pathological examination of the suspected lesions is also recommended.